Adaptação e validação de indicadores de qualidade do processamento de produtos na atenção primária à saúde - Passos, Isis Pienta Batista Dias (Universidade Federal de São Carlos, 2012)
The quality in processing health products is a pillar of infection prevention and control related to healthcare-associated infections (HAI). To evaluate these practices, quality indicators in health have been used to identify results and establish conformity rates. Indicators were developed to evaluate the hospital processing of dental-medicalhospital supplies (SÃO PAULO, 2006), but with the expansion of non hospital care and incipient publications on control and prevention of HAIs in these places, there is the need to use indicators in primary care. The present study therefore aimed to adapt and validate these indicators for use in the primary health care (PHC). It was used validation by expert consensus, with the participation of eleven judges. The adapted and validated instrument for use in PHC consists of nine indicators and components, being the main changes from the original, the inclusion of dental professionals in the supplies processing, the classification of Central Sterile Supply Departments (CSSD) in the PHC as Class I, the occurrence of chemical disinfection and the ratification of the sterilization using only moist heat. It was concluded that the established indicators for hospital use, after adaptation and validation, can be used in the PHC to evaluate the quality of the product processing. This is undoubtedly one of the priority measures for qualification and to advance in actions to control the HAI in these places.
Keywords: Enfermagem; Atenção primária à saúde; Esterilização; Indicadores de serviços; Estudos de validação; Primary health care; Sterilization; Nursing; Service indicators; Validation studies as topic; CIENCIAS DA SAUDE::ENFERMAGEM